Enantioselective, Catalytic Fluorolactonization Reactions with a Nucleophilic Fluoride Source - Woerly, Eric M; Banik, Steven M; Jacobsen, Eric N (Journal of the American Chemical Society, 2016)
The enantioselective synthesis of 4-fluoroisochromanones via chiral aryl iodide-catalyzed fluorolactonization is reported. This methodology uses HF-pyridine as a nucleophilic fluoride source with a peracid stoichiometric oxidant and provides access to lactones containing fluorine-bearing stereogenic centers in high enantio- and diastereoselectivity. The regioselectivity observed in these lactonization reactions is complementary to that obtained with established asymmetric electrophilic fluorination protocols.